Association of circulating BMP9 with coronary heart disease and hypertension in Chinese populations - Liu, Rui; Hu, Wenjing; Li, Xiaoqiang; Pu, Danlan; Yang, Gangyi; Liu, Hua; Tan, Minghong; Zhu, Danping (BMC cardiovascular disorders, 2019)
Background Bone morphogenetic protein9 (BMP9) has been reported to have a role in vascular development. However, there is still a lack of information regarding the association between circulating BMP9 levels and cardiovascular disease in humans. The goal of this study is to measure circulating BMP9 concentrations in patients with essential hypertension (HTN), coronary heart disease (CHD) and HTN + CHD, and evaluates the relationship between circulating BMP9 and these cardiovascular diseases. Methods A total of 417 individuals were recruited for this cross-sectional study from June 2015 to December 2017. These subjects were screened for HTN and CHD. Circulating BMP9 concentrations were measured by ELISA. Results Circulating BMP9 concentrations were significantly low in HTN, CHD and HTN + CHD individuals relative to those of the healthy individuals. Circulating BMP9 correlated negatively with SBP, FIns and HOMA- IR in HTN patients and correlated negatively with FBG and 2 h-BG in CHD patients. In both HTN and CHD patients, circulating BMP9 correlated negatively with BMI, WHR, FAT%, BP and TG. Multivariate logistic regression analysis showed that circulating BMP9 levels were associated with HTN, HTN + CHD and CHD. Individuals with low quartile of circulating BMP9 had a significantly high risk of HTN or/and CHD as compared with those in high quartile. Conclusions BMP9 is likely to be a biomarker for cardiovascular disease in humans, and it may play a role in the progression of cardiovascular disease. Trial registration ChiCTR-OPC-14005324 .